ASUHAN KEPERAWATAN PADA KLIEN TN. E DENGAN PPOK (PENYAKIT PARU OBSTRUKSI KRONIS) DIRUANG ALAMANDA RUMAH SAKIT UMUM DAERAH PASAR MINGGU - Uthia Rizqoh Mufidah (2020)
Chronic Obstructive Pulmonary Disease (COPD) is a disease in the lung organs that occurs in the lung parenchyma (emfiema) or its channel with a chronic inflammatory response (bronchitis) due to harmful substances. The purpose of this case study is to analyze nursing care for clients. E with Chronic Obstructive Pulmonary Disease (COPD). The process of nursing care is carried out based on the standard of nursing care for five days of treatment on 3-7 March 2020 at Tn. E, 73 years old and male. The results obtained are the main nursing problems are the ineffectiveness of breathing patterns. The implementation of nursing focuses on monitoring speed, rhythm, depth and difficulty breathing or instructing how to breathe deeply while coughing effectively. Nursing interventions have a positive impact on clients seen in part by decreasing signs and symptoms of COPD. The follow-up plan for nursing services is expected to be maximized both individually and family